Antidiabetic and Antibacterial Activities of Syzygium cumini Seeds - Bhattarai, Bidhya; Khanal, Lekha Nath; Kalauni, Surya Kant (Journal of Nepal Chemical Society, 2024)
Bioactive compounds of plants have been used in treating various diseases from ancient times. In this study, Syzygium cumini seed extract was studied for its antioxidant, antibacterial, and anti-diabetic potentials. The antioxidant potential was evaluated by DPPH assay. Whereas, the antibacterial feature was tested against Staphylococcus aureus, Escherichia coli, Salmonella typhi, and Klebsiella pneumonia by agar well diffusion method. The in vitro anti-diabetic potential was performed by the α-amylase enzyme inhibition method using CNPG3 (2-chloro-4-nitrophenyl-α-D-maltotriose) as a substrate. The methanolic extract showed a total phenolic content of 128.8 ± 1.44 mg GAE/g and a total flavonoid content of 115.6 ± 8.01 mg QE/g. The extract scavenged free radicals where strong antioxidant activity was observed with IC50 values of 91.63 ± 6.54 μg/mL in the concentration range of 50-6.25 μg/mL. The DCM and EA fractions exhibited moderate antidiabetic potentials with IC50 values of 92.1 ± 0.5 μg/mL, 150.8 ± 0.8 μg/mL, and 42.2 ± 4.6 μg/mL in the concentration range of 400-25 μg/mL against acarbose standard having IC50 values of 6.02 ± 0.1 μg/mL in the concentration range 50-1.6 μg/mL. The methanolic extract having ZOI (19mm) showed antibacterial activity however standard neomycin demonstrated ZOI (22.5 mm) against S. aureus at the dosage of 50 μg/mL. Methanolic extract having ZOI (20 mm) demonstrated effective antibacterial activity when compared to standard neomycin with ZOI (15mm) against K. pneumonia at the dosage of 50 μg/mL.